Comparing 10‐yr renal outcomes in deceased donor and living donor liver transplants. (5th November 2015) - Sandal, Shaifali; Almudevar, Anthony; Parajuli, Sandesh; Bose, Anirban
Abstract: Few studies have explored whether the type of LT, deceased donor LT (DDLT) or living donor LT (LDLT), impacts long‐term renal outcomes. We performed a retrospective analysis of 220 LT recipients at our institution to study their renal outcomes at 10 yr. Exclusion criteria were age ≤ 18 yr, graft survival ≤6 months, and multiorgan transplants; 108 DDLTs and 62 LDLTs were eligible. At baseline, DDLTs had a lower eGFR than LDLTs and 10.2% of DDLTs were on dialysis as compared to 0% of LDLTs. At 10 yr, seven DDLT and three LDLT recipients required dialysis or renal transplant (p = 0.75). In recipients with graft survival >6 months, DDLTs had a slower decline in eGFR as compared to LDLTs (p < 0.01). Among LDLTs, the decline in eGFR continued over the entire 10‐yr period, whereas among DDLTs, the decline in eGFR slowed significantly after six months (p = 0.01). This difference between the two groups was not seen among patients in the highest quartile of baseline eGFR. Patient survival and graft survival were similar. In conclusion, the incidence of end‐stage renal disease was similar in both DDLT and LDLT patients, but LDLT recipients seem to have a more sustained decline in eGFR when compared with DDLT recipients.